Assessing the Effects of Market Power on Electricity Reliability in China: Toward a Green and Reliable Market - Liu, Minghui; Ju, Chunhua; Huang, Ruting (Frontiers in Energy Research, 2022)
The transition to a low-carbon power system is among the measures to forge green energy transition and carbon neutrality, where grid firms act a crucial role. In this context, this paper uses the provincial data from 2004 to 2017 to evaluate the impact of market power of grid companies on service quality in China. Panel dynamic ordinary least square (DOLS) and fully modified ordinary least square (FMOLS) models are employed. The findings indicate that higher market power has indeed reduced reliability measured by average outage duration. Renewable energy integration also has negative effects and reduces electricity reliability. Finally, the effects are also heterogeneous across the different regions. The results may also provide useful lessons for other developing countries aiming to improve the electricity supply chain.